Emotional education for sustainable development: a curriculum analysis of teacher training in Portugal and Spain - Cristóvão, Ana Maria; Valente, Sabina; Rebelo, Hugo; Ruivo, Ana Francisca (Frontiers in Education, 2023)
The challenges before us show that the current model of development of our societies is creating problems to our planet, such as the climate crisis, the increase in inequalities and the emergence of new phenomena of exclusion and social malaise. The 2030 Agenda for Sustainable Development has 17 Sustainable Development Goals (SDG) that define priorities for a more sustainable world. Education is one of the main ways to create a peaceful and sustainable world for the survival and prosperity of present and future generations. Literature has highlighted the importance of teachers' socio-emotional skills and the promotion of socio-emotional skills in their students. Emotional education proposes a new pedagogical paradigm, in which the individual is encouraged to develop intra and interpersonal skills, knowing how to creatively deal with their conflicts and those in the environment, and increasing their self-confidence and emotional balance. These skills contribute to achieving the objectives of the SDG. Based on these arguments, it is urgent to observe and systematise social-emotional education A documental analysis of the study plans of the degrees and masters that train Preschool Teachers and Primary Teachers in Portugal and Spain was carried out, with the aim of understanding whether these courses offer Emotional Education subjects. Study plans from 127 public and private higher education institutions, in both countries, were analysed. The analysis revealed that in Portugal, despite an increase in interest in issues of emotional intelligence in schools, this interest is not yet reflected in the initial training of Preschool Teachers and Primary Teachers (with only two Universities offering Emotional Education content, both private). In Spain there is already a considerable number of institutions (29) that offer Emotional Education, corresponding to only 30% of the universities listed. The results of this study indicate that there is still a way to go to make emotional education effective in the curricula of future teachers and thus contribute to achieve the SDG.